Optimizing the trickle algorithm - Djamaa, Badis; Richardson, Mark A. (Cranfield University, 2015)
The Trickle Algorithm has enjoyed much popularity and widespread as a basic network primitive ensuring low-cost data consistency in lossy networks. Trickle was shaped by the so called short-listen problem hence imposing a listen-only period. Such a period allows Trickle to robustly address the short-listen problem but at the expense of increased latency. In this letter, we introduce a simple yet powerful optimization to Trickle that can dramatically decrease Trickle’s latency with virtually no extra overhead to its robustness and scalability. Extensive simulation and testbed experiments are reported here with greater than a factor of 10 times decrease in propagation time.